The Phenomenon of Body Shaming and Speech Ethics Shifts among Societies and Social Media Users - Ernita Dewi; Arsyi Arsyi (Islah: Journal of Islamic Literature and History, 2022)
Body shaming refers to all the words offending someone's physique that seem normal when meeting someone called fat or too thin, the body is not ideal, the feet are too small, the hands are too big. It may sound normal, but those who get these statements suffer pain in their hearts and cause regret about their physical condition and go on a strict diet to look ideal. The body shaming phenomenon has now entered the realm of social media. Moreover, nearly all Indonesians have social media, and even worse, the wide access to social media makes body-shaming victims feel even more humiliated. While many people are still in denial about body shaming, considering it to be far-fetched, in reality, there are many victims of body shaming. This paper refers to several cases of body shaming in the real world and the virtual world. With the descriptive qualitative method of collecting data through observation and interviews, the author found the fact that body shaming is increasingly epidemic, especially in social media. When there is a photo of someone in cyberspace, there will definitely be negative comments that hurt. In fact, it is often likened to an animal, such as describing someone as a lumoe (ox), this happens in the social media user community in Aceh. Even though this behavior and speech are very contrary to the customs of the Acehnese people who uphold the teachings of Islam, the current conditions with the enormous openness to social media, da'wah for bad speech looks more massive than speech that is full of adab and politeness.